2016
DOI: 10.1051/limn/2016023
|View full text |Cite
|
Sign up to set email alerts
|

Sediment chemistry and flooding exposure: a fatal cocktail forPhragmites australisin the Mediterranean basin?

Abstract: The common reed die-back syndrome was formerly reported mostly in Central Europe and more recently in the Mediterranean basin. This study investigates a case of reed die-back in Central Italy through a Geographic Information System (GIS) diachronic survey and the analysis of macromorphological and ecological parameters. Data were recorded during field activities on ten plots randomly distributed according to two ecological statuses, permanently and temporarily flooded. Culm density, height and diameter, clumpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
(71 reference statements)
1
20
0
Order By: Relevance
“…Even if this species sometimes shows an expansive behavior ( Bertness et al, 2002 ; Foggi et al, 2011 ), since the 1950s an irreversible retreat of the population known as reed die-back syndrome (RDBS) has been observed from several wetlands of northern and central Europe (for a review, see van der Putten, 1997 ). In Italy, it was first detected in a brackish lagoon ( Fogli et al, 2002 ), and recently in freshwater lakes ( Gigante et al, 2011 , 2014 ; Lastrucci et al, 2016a ). Typical symptoms of RDBS include reduced plant height, weaker culms, abnormal rhizomes, formation of clumps ( Armstrong et al, 1996 ; Fogli et al, 2002 ), and eventually retreat of the population ( van der Putten, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even if this species sometimes shows an expansive behavior ( Bertness et al, 2002 ; Foggi et al, 2011 ), since the 1950s an irreversible retreat of the population known as reed die-back syndrome (RDBS) has been observed from several wetlands of northern and central Europe (for a review, see van der Putten, 1997 ). In Italy, it was first detected in a brackish lagoon ( Fogli et al, 2002 ), and recently in freshwater lakes ( Gigante et al, 2011 , 2014 ; Lastrucci et al, 2016a ). Typical symptoms of RDBS include reduced plant height, weaker culms, abnormal rhizomes, formation of clumps ( Armstrong et al, 1996 ; Fogli et al, 2002 ), and eventually retreat of the population ( van der Putten, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the possible abiotic and biotic causes of reed decline has been widely investigated ( Brix, 1999 ; Fogli et al, 2002 ). Among the abiotic factors, prolonged submersion of the plant appears to have dramatic consequences; Lastrucci et al (2016a) demonstrated the existence of a relationship between reed die-back and permanent-artificially induced flooding conditions. Several macromorphological traits associated with RDBS (such as clumping habit, reduced culm height or diameter, high rate of dead buds, see Gigante et al, 2011 , 2014 ; Lastrucci et al, 2016a for details) were significantly more often observed in permanently flooded stands than in the emerged stands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies related to growth form and performance of Phragmites australis found significant differences in attributes according to site-specific ecological status. Flooded stands or sites with permanent submersion were characterized by high rates of clumping habit and dead apical bud, and lower culm diameters, showing clear signs of plants dieback (Lastrucci et al 2016(Lastrucci et al , 2017. Other studies addressed the growth response of a rare fern, Marsilea quadrifolia, and a widespread opportunistic species, Vallisneria spiralis, respectively to sediment trophic level and physicochemical water features, demonstrating a certain capacity of both species to grow under varying levels of nutrients in water and sediment (Bolpagni & Pino 2017;Bolpagni et al 2015).…”
Section: Aquatic Environments and Plant Growth: Evidence From River Amentioning
confidence: 99%